Relationship of Patient Safety Culture with Social Intelligence and Psychosocial Factors in the Workplace among Nurses Working in the Pediatric Wards of West Guilan Hospitals, Iran, 2020 - Robabeh Ansari; Narges Sadeghi; Maryam Moghimian (Hamadan University of Medical Sciences, 2022)
Background and Objective: This study aimed to determine the relationship of patient safety culture with social intelligence and psychosocial factors in the workplace among nurses working in the pediatric wards of West Guilan hospitals, Iran, in 2020. Materials and Methods: In this descriptive-correlational cross-sectional study, 130 nurses working in the pediatric wards of West Gilan hospitals in 2020 were selected using the availability sampling method. The required data were collected using the Hospital Survey on Patient Safety Culture, Social Intelligence Questionnaire (Silura et al., 2001), and the Psychosocial Factors Questionnaire (Christensen et al., 2005). Finally, the collected data in SPSS-23 statistical software were analyzed at both descriptive and inferential levels. Results: The results showed that patient safety culture, social intelligence, and psychosocial factors were at lower than average, higher than average, and average levels, respectively, in nurses working in the pediatric wards of West Gilan hospitals in 2020. There were significant relationships between patient safety culture and social intelligence (r=0.756) and between patient safety culture and psychosocial factors in the workplace among the studied nurses (r=0.878). Conclusion: Based on the findings, patient safety culture had a positive relationship with social intelligence and psychosocial factors in the workplace among nurses working in the pediatric wards of West Gilan hospitals in 2020.